EFFECT OF FATIGUE ON THE TARGET ACCURACY OF TECHNIQUES IN SPORTS GAMES - Artikov, Askar (Журнал иностранных языков и лингвистики, 2022)
The paper presents the results of a study of factors affecting the target accuracy of shots in basketball and handball. The effect of fatigue on the effectiveness of throws after heavy glycolytic loads has been studied, data on the rate of recovery of the functional systems of the body of young athletes are presented. The results of the study can be used by specialists working with young athletes in sports games.